Interventions for preventing, delaying the onset, or decreasing the burden of frailty: an overview of systematic reviews. Issue 1 (December 2015) - Wilson, Michael; Béland, François; Julien, Dominic; Gauvin, Lise; Guindon, G.; Roy, Denis; Campbell, Kaitryn; Comeau, Donna; Davidson, Heather; Raina, Parminder; Sattler, Deborah; Vrkljan, Brenda
Abstract Background Many systematic reviews have evaluated the effectiveness of interventions to prevent, delay, or decrease frailty symptoms, but no effort has been made to identify, map, and synthesize the findings from reviews across the full spectrum of interventions. Our objectives are to (1) synthesize findings from all existing systematic reviews evaluating interventions for preventing, delaying the onset, or decreasing the burden of frailty symptoms; (2) examine different conceptualizations of frailty that have been used in the development and implementation of interventions; and (3) inform policy by convening a stakeholder dialogue with Canadian health-system leaders. Methods/design We will conduct an overview of systematic reviews to identify and synthesize all of the systematic reviews addressing interventions to preventing, delaying the onset, or decreasing the burden of frailty symptoms. To identify relevant systematic reviews, we will conduct database searches for published and grey literature as well as contact key experts and search reference lists of included reviews. Two reviewers will independently review all search results for inclusion and then conceptually map, extract key findings (including the conceptualization/definition of frailty used) and assess the methodological quality of all included reviews. We will then synthesize the findings by producing a 'gap map' (i.e. mapping reviews in a matrix according to the interventions and outcomes assessed), and narratively synthesize the key messages across reviews related to type of interventions. Discussion Following the completion of the synthesis, we will use the findings to develop an evidence brief that mobilizes the best available evidence about the problem related to preventing, delaying the onset, or decreasing the burden of frailty symptoms in older adults, policy and programmatic options to address the problem and implementation considerations. The evidence brief will then be used as the input into a stakeholder dialogue, which will engage 18–22 Canadian health-system leaders (including policymakers, health providers, researchers, and other stakeholders) in 'off-the-record' deliberations to inform future actions and policymaking. Systematic review registration PROSPEROCRD42015022082